Nitrogen and Ammonia Mitigation on Laying Hen Farms: Effects of Low-protein Diet and Manure Filtering - Silaban, Rikardo; Sumiati, Sumiati; Adrizal , Adrizal; Yusrizal, Yusrizal; Sumadja, Wiwaha Anas; Yatno, Yatno; Noferdiman, Noferdiman; Koh, Katsuki; Rahman, Mustanur (International Journal of Poultry Science, 2017)
Background: Lowering dietary Crude Protein (CP) has been widely reported as a method to reduce nitrogen (N) excretion, but information on its effect in combination with filtering by Azolla pinnata to further mitigate N or ammonia (NH3) volatilization from laying hen manure is limited. Materials and Methods: Two experimental diets containing 17% (control) and 15% (low) crude protein were assigned to 2 groups of 22 weeks old ISA Brown hens, so each treatment had 20 replicates with 6-7 birds each. The manure from each group was flushed into two terraced ponds, in which Azolla pinnata was grown in the lowest terrace to filter the N in the sludge. Fresh manure was collected when the hens were 29 weeks old to analyze the N and NH3 contents and perform microbial counts and analyses of pond water quality (total dissolved solubles, temperature and pH), Azolla N and egg quality were conducted. Data were subjected to either a one or two-way ANOVA. Results: Lowering dietary crude protein to 15% resulted in a 21.83% (p<0.05) decrease in manure NH3, but it did not alter the microbial counts or N content. Additionally, pond water quality was not affected by dietary CP, the presence of Azolla in the pond or the dietary crude protein×Azolla interaction and there was no difference in the N content of the Azolla biomass among dietary groups. Eggs laid by hens given the low-CP diet had comparable quality to those laid by the control hens. Conclusion: Reducing dietary crude protein to 15% lowered NH3 volatilization and did not negatively affect egg quality. However, growing Azolla in a terraced pond failed to elicit an N-filtering effect.